The Relationship between Psychological Stress and the Menstrual Cycle in Eighth Grade Female Adolescents at SMP Negeri 3 Panyabungan Regency Mandailing Natal - Sri Wahyuni Harahap; Ayu Ulfah Nur Lubis; Doriana harahap; Nur Hasanah siregar; Ennysah Hasibuan; Doriani Harahap (International Journal of Public Health Excellence (IJPHE), 2026)
The menstrual cycle is the time from the first day of menstruation until the next menstrual cycle, while the length of the menstrual cycle is the distance from the start date of the previous menstruation to the start of the next menstrual cycle. A woman's menstrual cycle is usually 21-35 days, only 10-15% of women have a cycle of 28 days, 3-5 days and some have 7-8 days. Stress is an individual's response to changes in a threatening situation, This can be seen as a personal reaction to external events or demands such as doing tasks or internal states of mind such as worry. Stress tends to increase when unable to cope with unpleasant situations faced by a person. The population in this study was 47 people. The sample in this study used a Total Sampling sampling technique, namely a sampling technique where the sample size is the same as the population. The type of research used in this study is descriptive analytic with the Cross sectional method. The results of this study indicate that the p value = 0.050 (p = 0.05), so it is concluded that Ho is rejected and Ha is accepted. It is recommended for female students to continue to understand how to manage stress and reproductive health and to be able to carry out activities that are expected to reduce stress levels and seek information related to stress management and reproductive health